Interculturalidade: Sopro do Espírito na vida dos cristãos andinos (Razão e Fé, 2023)
The present article, by way of essay, values the intercultural experience of the Andean Christians, understood as a manifestation of their own Spirit. The text is inserted into the indigenous theological journey in the Andean context. It values the experience, the categories proper to the culture mentioned, the theological production of autochthonous authors and inserted into reality, in search of an inculturated pneumatological synthesis.